DE VOLTA AO QUARTO DE MARY - Cavalcante Barroso , Cícero Antônio (Prometheus - Journal of Philosophy., 2020)
In this article, I present an analysis of the Knowledge Argument (KA), as formulated in Jackson (1982) on basis from Mary's story, as well as of some of the main objections addressed to it. After pointing out the reasons why I think the KA escapes these objections, I offer an objection that seems to me to be unavoidable and that considerably reduces the CA's offensive power against physicalism.